A Study on the Factors Influencing AI Recruitment Bots in Terms of Filtering Right Profiles with Reference to IMEJOB - Surjadeep Dutta, Victor Mondal, Agnideep Datta, Arivazhagan.R, Shyamaladevi.B (European Economic Letters (EEL), 2024)
Background: Historically, the process of recruiting has required a significant amount of manual effort and has taken up a considerable amount of time. Artificial Intelligence (AI) has revolutionised recruitment software, making it more efficient and effective in optimising hiring procedures. This paper examines the tactics utilised by AI-based recruiting software, with a specific focus on the instance of IMEJOB, to effectively filter and match the most appropriate individuals with the appropriate job vacancies. Objective: The objective of the study is to analyse the key factors that influence AI based recruitment software in filtering right profiles. Methodology: Quantitative data is collected by analysing recruiting parameters such as time saving recruitment, quality recruitment, and cost- effective recruitment before and after the adoption of IMEJOB. Qualitative data is obtained by conducting interviews with HR professionals and recruiters who utilise IMEJOB, in addition to administering surveys to candidates who have had interactions with the system. Around 150 samples have been collected for this study. The data has been collected in Bangalore. The collected data has been transferred to IBM SPSS for further analysis followed by Chi Square analysis and Regression Analysis. Analysis: Chi Square Analysis and Regression Analysis has been conducted. HR experts have provided feedback indicating a notable degree of contentment with the AI system, highlighting improved productivity and diminished prejudice in the hiring procedure. Conclusion: AI-powered recruiting software, such as IMEJOB, has significant potential to revolutionise conventional hiring procedures. By using sophisticated AI approaches, the selection process for candidates is enhanced, resulting in a more accurate matching of suitable profiles with appropriate opportunities. This not only improves the efficiency of the recruitment process but also increases organisational productivity by providing a more suitable alignment between personnel and their respective tasks. The transformative influence of the unique platform at IMEJOB in the field of AI-based recruitment is shaped by factors such as time-saving, quality, cost-effectiveness, and brand image. By incorporating AI algorithms, IMEJOB is able to transform conventional hiring procedures by quickly analysing extensive candidate databases, pinpointing exceptional individuals, and automating monotonous chores, resulting in a substantial reduction in the time it takes to hire. This increased efficiency not only speeds up the process of hiring new employees, but also improves the overall quality of hires by using innovative methods to screen candidates and engage with them on a personal level.